The Trick to Money is Having Some! - Wilde, Stuart (new Mexico White Dove International, Inc., 1989)
Deals with the E S P of easy money and the metaphysics of being in the right place at the right time, with the right idea and the right attitude. This book shows you that money is merely a form of energy - and that the difference between having it and not having it is merely a small but subtle shift in consciousness.
Include Appendix.
Keywords: Finance, Personal -- Finance -- Personal